Study of the frequency of female genital tract infection using cartridge based nucleic acid amplification test - Chaudhary, Drishti; Tyagi, Mamta; Gupta, Smriti; Yadav, Lalita; Pandey, Anita (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2022)
Background: The aim of the study was to study the frequency of female genital tract infection using cartridge based nucleic acid amplification test (CBNAAT), to study the sensitivity, specificity, positive predictive value, negative predictive value and diagnostic accuracy of CBNAAT. Methods: This prospective observational study was conducted among 100 patients as per inclusion criteria with genital tract infection in Swami Vivekanand Subharti University, Meerut over a period of two years. Investigations including ZN staining for acid fast bacillus (AFB), endometrial sampling for histopathology, CBNAAT and BACTEC culture were sent. Results: In a study of 100 patients’ histopathological examination detected tuberculosis in 2% patients while CBNAAT detected tuberculosis in 5% patients. Tubercle bacilli was found in 3% women on AFB stain while in only 1%-woman genital tuberculosis was diagnosed by BACTEC culture. Conclusions: Female genital tuberculosis is detected most frequently when a woman presents with unexplained infertility. Newer technologies allow genital tuberculosis to be identified at an earlier stage and enable us to provide treatment. CBNAAT being a sensitive test picked up more cases than histopathology, culture, AFB stain. Hence CBNAAT should be widely used for early detection of female genital tuberculosis.